Meta-analysis of the prevalence of renal cancer detected by abdominal ultrasonography. Issue 6 (13th April 2017) - Rossi, S H; Hsu, R; Blick, C; Goh, V; Nathan, P; Nicol, D; Fleming, S; Sweeting, M; Wilson, E C F; Stewart, G D
Abstract: Background: The potential for an ultrasound-based screening programme for renal cell carcinoma (RCC) to improve survival through early detection has been the subject of much debate. The prevalence of ultrasound-detected asymptomatic RCC is an important first step to establishing whether a screening programme may be feasible. Methods: A systematic search of MEDLINE and Embase was performed up to March 2016 to identify studies reporting the prevalence of renal masses and RCC. Two populations of patients were chosen: asymptomatic individuals undergoing screening ultrasonography and patients undergoing ultrasonography for abdominal symptoms not related to RCC. A random-effects meta-analysis was performed. Study quality was evaluated using a validated eight-point checklist. Results: Sixteen studies (413 551 patients) were included in the final analysis. The pooled prevalence of renal mass was 0·36 (95 per cent c.i. 0·23 to 0·52) per cent and the prevalence of histologically proven RCC was 0·10 (0·06 to 0·15) per cent. The prevalence of RCC was more than double in studies from Europe and North America than in those from Asia: 0·17 (0·09 to 0·27) versus 0·06 (0·03 to 0·09) per cent respectively. Data on 205 screen-detected RCCs showed that 84·4 per cent of tumours were stage T1–T2 N0, 13·7 per cent were T3–T4 N0, and only 2·0 per cent had positive nodes or metastases at diagnosis. Conclusion: At least one RCC would be detected per 1000 individuals screened. The majority of tumours identified are early stage (T1–T2). Abstract : 1:1000